186k views
5 votes
Using the quadratic formula to solve, which of the following choices below will simplify to the correct solution of 3x^2 + 4.3x - 4 = 0?

A. -4 + 16 - 48 / 6
B. 4 + 16 + 48 / 6
C. -4 + 16 + 48 / 6
D. 2 / -6

User DeGo
by
7.0k points

1 Answer

3 votes

Final answer:

To solve the equation 3x^2 + 4.3x - 4 = 0 using the quadratic formula, substitute the values into the formula and simplify to find x = -0.576 or -2.743.

Step-by-step explanation:

To solve the equation 3x^2 + 4.3x - 4 = 0 using the quadratic formula, we can compare it to the standard form ax^2 + bx + c = 0 and identify a = 3, b = 4.3, and c = -4.

Using the quadratic formula, x = (-b ± √(b^2 - 4ac)) / (2a),

Substituting the values, x = (-4.3 ± √(4.3^2 - 4(3)(-4))) / (2(3))

Simplifying further, x = (-4.3 ± √(18.49 + 48)) / 6 which is equivalent to x = (-4.3 ± √66.49) / 6

The simplified correct solution is therefore x = (-4.3 ± 8.16) / 6, which is the same as -4.3 + 8.16 / 6 or -4.3 - 8.16 / 6 = -0.576 or -2.743.

User Peoray
by
7.2k points